2012
DOI: 10.25011/cim.v35i5.18697
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Molecular Targets for the Treatment of Medulloblastomas

Abstract: Purpose: To present an assortment of molecular targets evident from a variety of signal transduction pathways and downstream e ectors, which may have clinical relevance for the treatment of medulloblastomas.Source: Data were archived from MEDLINE, using Boolean-formatted queries on the keywords including: medulloblastoma, pathology, prognosis, classi cation, tumor regression, inhibition, therapy, clinical trial, therapeutic agent, drug, molecular inhibitor, and signalling pathway. Only the most reputable artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 94 publications
(124 reference statements)
0
5
0
Order By: Relevance
“…In the CNS, STAT3 is a potential target in the prevention and the treatment of medulloblastoma (Ajeawung et al, 2012) and glioblastoma multiforme, the most common and aggressive primary brain tumour (Luwor et al, 2013). STAT3 inhibition also prevents ischaemic brain injury and has a therapeutic potential for ischaemic strokes .…”
Section: Figurementioning
confidence: 99%
“…In the CNS, STAT3 is a potential target in the prevention and the treatment of medulloblastoma (Ajeawung et al, 2012) and glioblastoma multiforme, the most common and aggressive primary brain tumour (Luwor et al, 2013). STAT3 inhibition also prevents ischaemic brain injury and has a therapeutic potential for ischaemic strokes .…”
Section: Figurementioning
confidence: 99%
“…More recently, Simpson et al showed that IGF-1R targeting increased the radio-sensitivity of pHGG cells, likely through perturbation of the DNA damage response [ 14 ]. Of relevance, IGF-1R was also identified as a therapeutic target in medulloblastoma, a highly aggressive pediatric malignancy of the cerebellum [ 29 , 30 ]. Collectively, the results suggest that IGF-1R targeting may have beneficial therapeutic effects in pediatric brain malignancies, including pHGG.…”
Section: Discussionmentioning
confidence: 99%
“…Myc inhibition for cancer therapy has been investigated over the years with little success. Nevertheless, agents that target Myc such as S2T1–6OTD, a telomestatin derivative that can bind to the c-Myc promoter, as well as agents that can modulate Myc expression including all- trans -retinoic acid (ATRA), the quassinoid analog NBT-272, the anti-convulsant and HDAC inhibitor-valproic acid (VPA), the polyphenol resveratrol, have shown efficacy in vitro and in mice, and their further investigation in MYC-high MBs may be warranted [76,77]. The availability of three separate Myc-driven mouse models of LCA MB should further aid in such preclinical studies [7881].…”
Section: Groupmentioning
confidence: 99%